Nilai-Nilai Patriotisme Pada Lirik Lagu Los! Los! Los! Karya Hotaru Kajian Semiotika Riffaterre - Hastuti, Nur; Fakhliza, Shaila (KIRYOKU, 2025)
This article analyzes the value of patriotism in the lyrics of the opening song of a Japanese animation titled "Los! Los! Los!" by Hotaru which was released on February 22, 2017. This research aims to reveal the values of patriotism reflected in the figure of a soldier in defending his country with Riffaterre's semiotic theory. This research uses a qualitative descriptive method. Song lyrics are analyzed through the process of heuristic reading, hermeneutic reading, matrix, model, variant, and hypogram. The results found are; based on heuristic reading, the lyrics of the song "Los! Los! Los!" tells the heart of a person who fights against an enemy country by sacrificing his life. In hermeneutic reading, the meaning of the song lyrics “Los!” Los! Los!" is not only about sacrifice and loyalty to the country, but the courage to lead the troops with optimism to achieve peace. Variants of the song's lyrics are battle and sacrifice. The hypogram in the lyrics of the song "Los! Los! Los!“ is a potential hypogram ”from beginning to end this battle is futile". The hypogram is adjusted based on the matrix and variants contained in the song lyrics about the war that sacrificed many soldiers' lives. Through the lyrics, there is the value of patriotism shown by “I” which includes love for the country, unity, willing to sacrifice for the sake of creating peace in the country.